The Arab historians ’ view of the History of the Ottoman existence, between Ideology and Academic Writing - mouloua, amina (The Algerian Historical Journal, 2026)
This study aims to investigate the different Arab views on the history of the Ottoman state in general and the Ottoman presence in the Arab countries in particular. By highlighting the owners of the national ideological orientation who condemned the Ottoman state and over-criticized it, influenced by the ideas of the Colonial School and the writings of European Orientalists, which often carried a misleading character, and the Islamic current that over-revered it as the last Islamic State and caliphate. In contrast to these two trends, a class of historians emerged who sought to reassess the Ottoman presence in the Arab countries, from an objective scientific perspective, based on a careful research methodology, relying on original documents, and referring to the basic Arab and Ottoman sources, including books and manuscripts, with the aim of a balanced reading of Ottoman history, according to a critical vision devoid of prejudices and ideological influence, both emotional and influenced by Orientalist prejudices.